Tribological Behavior of High-Strength Aluminum Alloys in Combination with Dry Lubricants at High Forming Temperatures - Rigas, Nikolaos; Junker, Friedhelm; Berendt, Erik; Merklein, Marion (Defect and Diffusion Forum, 2022)
High-strength aluminum alloys provide great potential for weight reduction in vehicle and aircraft production. Nevertheless, forming of these materials is limited at room temperature. Thermally supported forming operations such as hot forming and quenching (HFQ®) allow forming of components without failure and reduced springback. Currently, the adhesive wear and high friction limit the use of HFQ®-operations for high-strength aluminum alloys. Out of this reason, the present paper describes the tribological performance of new developed dry lubricants at elevated temperatures for the alloy AA7075. For this purpose, strip drawing tests were carried out in a modified open tribological system at temperatures between 20 °C and 400 °C. Additionally, the melting behavior of these lubricants, as well as the variation of the lubricant thickness, were investigated. The results show a reduction of the coefficient of friction at elevated temperatures.
Keywords: Tribology; Hot stamping; Lubrication; High-strength aluminum